Outcome of International Federation of Gynecology and Obstetrics Stage IIB Cervical Cancer From 2003 to 2012. Issue 5 (June 2015) - Guo, Lili; Liu, Xiaoyan; Wang, Lin; Sun, Haiying; Huang, Kecheng; Li, Xiong; Tang, Fangxu; Li, Shuang; Yuan, Xianglin; Wang, Changyu
<x xml:space="preserve">Abstract</x> Objective To compare the clinical outcomes of patients with International Federation of Gynecology and Obstetrics (FIGO) stage IIB cervical carcinoma receiving neoadjuvant chemotherapy followed by radical hysterectomy (RH) with those of patients receiving chemoradiation therapy (CRT) alone. Methods We retrospectively reviewed the medical records of patients with FIGO stage IIB cervical carcinoma. A total of 621 patients were eligible for the study according to the surgery-based or radiotherapy-based treatment; 285 patients received cisplatin-based neoadjuvant chemotherapy (NACT) followed by RH, and 336 patients underwent sequential or concurrent chemoradiation. The disease-free survival, overall survival, recurrence rates, and late complications were compared. Cox regression analysis was used to identify potential prognostic factors. Results Complete or partial response was seen in 77.6% (221/285) of the NACT-treated patients. Disease-free survival and overall survival rates of the patients who had NACT-sensitive responses were significantly higher than those who did not response (P = 0.021 and P = 0.008). Overall survival rates in the NACT + RH group were comparable with the concurrent chemoradiotherapy or chemoradiation groups (P > 0.05). Neoadjuvant chemotherapy followed by RH significantly decreased the recurrence rate (22.6% vs 35.5%), resulted in fewer treatment-related complications, and ultimately improved survival when compared with concurrent CRT. A survival benefit was observed for 63.9% of the patients in the NACT + RH group without adjuvant radiotherapy or CRT. Conclusions Compared with concurrent chemoradiotherapy, NACT followed by RH achieved comparable survival outcomes for patients with FIGO stage IIB cervical cancer. This treatment method was significantly effective at reducing radiotherapy rates and complications, and it is worthy of recommending for younger patients.